Multistate reptile‐ and amphibian‐associated salmonellosis outbreaks in humans, United States, 2009–2018. (10th August 2022) - Waltenburg, Michelle A.; Perez, Ariana; Salah, Zainab; Karp, Beth E.; Whichard, Jean; Tolar, Beth; Gollarza, Lauren; Koski, Lia; Blackstock, Anna; Basler, Colin; Nichols, Megin
Abstract: Non‐typhoidal Salmonella cause an estimated 1.4 million human illnesses, 26, 000 hospitalizations and 400 deaths annually in the United States. Approximately 11% of these infections are attributed to animal contact. Reptiles and amphibians are known sources of salmonellosis; young children (aged <5 years) are disproportionately affected by reptile‐ and amphibian‐associated salmonellosis (RAAS) outbreaks. We describe multistate RAAS outbreaks to characterize illnesses and inform prevention efforts. RAAS outbreaks were defined as ≥2 culture‐confirmed human Salmonella infections with similar pulsed‐field gel electrophoresis patterns and epidemiologic, laboratory or traceback evidence linking them to a common reptile/amphibian exposure. Data sources included the Animal Contact Outbreak Surveillance System; CDC Outbreak Response and Prevention Branch's outbreak management database; PulseNet, the national molecular subtyping network for foodborne disease surveillance in the United States; and the National Antimicrobial Resistance Monitoring System. Twenty‐six RAAS outbreaks were reported during 2009–2018, resulting in 1465 illnesses and 306 hospitalizations. The outbreaks were associated with turtles (19), lizards (5), snakes (1) and frogs (1). Sixteen (61.5%) outbreaks were linked to small turtles (<4 inches), resulting in 914 illnesses. Forty‐nine percent of outbreak‐associated patients were aged <5 years. Of 362 patients/caregivers interviewed, 111 (30.7%) were aware that reptiles/amphibians can carry Salmonella . Among 267 patient isolates with antimicrobial susceptibility information, 20 (7.5%) were non‐susceptible to ≥1 antibiotic used to treat human salmonellosis. RAAS outbreaks result in considerable morbidity, particularly among young children. Illnesses linked to small turtles are preventable through education, targeted outreach to caregivers and paediatricians, and when appropriate, enforcement. Historically, individual states and jurisdictions have enforced existing or promulgated new authorities to address outbreaks. Preventing future RAAS outbreaks requires addressing challenges related to the illegal sale/distribution of small turtles; and for legal reptile sales, providing information on RAAS risk to consumers at point of sale to support informed pet ownership decisions.